2014
DOI: 10.3892/ol.2014.2654
|View full text |Cite
|
Sign up to set email alerts
|

Primary ameloblastic carcinoma of the maxilla: A case report and literature review

Abstract: Ameloblastic carcinoma (AC) is a rare malignant odontogenic neoplasm that tends to occur in the mandible rather than in the maxilla. This malignancy is classified as a tumor that combines the morphological features of ameloblastoma and carcinoma, regardless of the presence or absence of metastasis. In addition, AC has been classified into two types, primary and secondary. The former develops de novo and the latter develops by malignant transformation of a pre-existing benign ameloblastoma. The present study de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 30 publications
(27 reference statements)
1
31
0
Order By: Relevance
“…In the present study, we assessed 17 newly reported cases of maxillary AC from 2009 to 2017 (see Table 1). [2,6,[8][9][10][11][12][13] The age ranges from 21 to 77 years (mean age: 57.1 years) and the male to female ratio was 7.5:1, which was consistent with the Kruse et al report. [3] Most of the lesions (88.2%) similar to the present case and to previously reported cases occurred in the posterior portion of the maxilla.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In the present study, we assessed 17 newly reported cases of maxillary AC from 2009 to 2017 (see Table 1). [2,6,[8][9][10][11][12][13] The age ranges from 21 to 77 years (mean age: 57.1 years) and the male to female ratio was 7.5:1, which was consistent with the Kruse et al report. [3] Most of the lesions (88.2%) similar to the present case and to previously reported cases occurred in the posterior portion of the maxilla.…”
Section: Discussionsupporting
confidence: 80%
“…Cortical bone perforation, soft tissue invasion and nasal cavity involvement have been documented in previously reported cases. [7,9,12] Microscopically, AC often retains some histopathologic aspects of ameloblastoma such as inverse nuclear polarization and peripheral palisading in tumoral islands, demonstrating plexiform and follicular patterns, combined with histologic features of malignancy like hyperchromatism, pleomorphism, atypical mitoses, vascular and neural invasion and tissue necrosis. Spindle cell and clear cell-rich variants, and also a few cases with squamous differentiation have been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,16,17 Metastatic lesions were detected in 22% of conventional ameloblastic carcinomas, except in the spindle cell variant. 15 Uzawa et al 18 reported that the recurrence rate of ameloblastic carcinoma was 38.4%. It has been reported that the period of recurrence and distant metastasis of ameloblastic carcinoma is longer than that of the head and neck squamous cell carcinomas.…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that the period of recurrence and distant metastasis of ameloblastic carcinoma is longer than that of the head and neck squamous cell carcinomas. 18 The average recurrence period from primary treatment was 47.5 months. The difference in mean ages for the two lesions suggests that more genomic changes are required to develop spindle cell variant of ameloblastic carcinoma compared with ordinary ameloblastic carcinoma.…”
Section: Discussionmentioning
confidence: 99%